ANALISIS PENGARUH CITRA PERUSAHAAN, PERATURAN PEMERINTAH, HARGA, DAN KUALITAS PRODUK TERHADAP UPAYA MEMBENTUK PERSEPSI MASYARAKAT TENTANG PRODUK RAMAH LINGKUNGAN (Studi pada Masyarakat di Sukoharjo) - Widiastuti, Erni (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2019)
The purpose of this study is to determine and measure the influence of company image, environmental regulations, price and product quality both partially and simultaneously on efforts to shape public perceptions about environmentally friendly products. The hypotheses in this study are: It is suspected that the company's image, environmental regulations, product prices and quality have a significant effect both partially and simultaneously on efforts to shape public perceptions about environmentally friendly products. The data needed in this study are primary data obtained by the questionnaire method of a sample of 100 respondents. Data analysis used in this research is multiple linear regression test, t test, F test and coefficient of determination test. The results of data analysis in this study can be concluded that the company's image, environmental regulations, product prices and quality have a significant positive effect both partially and simultaneously on efforts to shape public perceptions about environmentally friendly products. Judging from the magnitude of the coefficient of determination (adjusted R square) which has a positive value of 0,827, it shows that people's perceptions about environmentally friendly products are explained by variables of company image, environmental regulations, and price and product quality by 82,7% and the rest by 17,3% represents other free variations that were not observed in this study.